Debureaucratization limits in administrative procedures codification: Lessons from Slovenia - Polonca Kovač (Administrative Sciences, 2021)
This article explores bureaucratization and its boundaries in the framework of cutting red tape in the regulation of administrative procedures. Law is not an end in itself but should contribute to predictable and thus better relations in society. In this sense, the priority protection of public interest-which is characteristic of administrative relations between individual holders of rights and obligations and administrative bodies-presents certain limitations to simplification. Through qualitative research methods (dogmatic, normative, and comparative methods, as well as case studies), this article examines examples of debureaucratization in Slovenia provided by the amendments to the General Administrative Procedure Act. In most cases, e.g., in waiving the right to appeal or broad fiction of service, modifications were not appropriate since constitutional guarantees cannot be subject to "debureaucratization". However, crises such as the COVID-19 pandemic call for even greater simplification. The approach to address bureaucratization as an obstacle to the economy should therefore be holistic and proportionate. Debureaucratization should be implemented in individual administrative areas rather than by an umbrella law that ensures fundamental administrative principles, and through process optimization rather than deregulation. The results of the analysis are useful for comparable, particularly Central European countries.
Keywords: 350; administrative procedures; codification; debureaucratization; public interest; Slovenia